Room for improvement? : relocating a business school - Angwin, Duncan (SAGE Knowledge. Cases., 2016)
The case fbfb the transition of Oxford Brookes' business school to a new building on the university campus outside of the city of Oxford and how management dealt with concerns to do with the new working space and adapted their original design to ensure greater student satisfaction.